Research on the effect of Rosa roxburghii root in alleviating spleen and stomach damp–heat gastric ulcer by regulating the imbalance of oral–gut axis microbiota - Cao, Jiangsong; Zhang, Ziyu; Liu, Xiongwei; Zhou, Ying; Li, Jiaxin; Wang, Xinyue; Liu, Chang (Frontiers in Microbiology, 2025)
BackgroundRosa roxburghii root (RT), a medicinal herb traditionally utilized by ethnic minorities in Guizhou Province, has demonstrated potential in managing gastrointestinal disorders. Nonetheless, its effectiveness in treating gastric ulcers (GU) accompanied by spleen–stomach damp–heat syndrome, especially through mechanisms that involve interactions with oral–gut microbiota, remains to be elucidated.MethodsA rat model of GU with damp–heat syndrome was established. The rats were treated with various doses of RT, and gastric mucosal injury was assessed through ulcer index calculation and histopathological examination. Additionally, the levels of immunoglobulin 6 (IL-6), tumor necrosis factor alpha (TNF-α), nitric oxide (NO), inducible nitric oxide synthase (iNOS), motilin (MTL), prostaglandin E2 (PGE2), and malondialdehyde (MDA) were measured. A 16S ribosomal RNA (rRNA) sequencing was conducted on samples of tongue coating and intestinal contents to analyze the microbial composition and changes.Results and discussionCompared to the control (CON) group, the gastric ulcer (GU) group exhibited significant pathological alterations in the gastric mucosa. The levels of IL-6, TNF-α, and MDA were significantly elevated (p < 0.01), whereas the levels of NO, iNOS, MTL, and PGE2 showed a notable reduction (p < 0.01). Compared to the GU group, the RT’s high-dose (RTH) groups exhibited statistically significant improvements in the ulcer index, reduced levels of TNF-α, IL-6, MDA, and increased levels of NO, MTL, iNOS, and PGE2 (p < 0.05). Moreover, RT reversed oral–gut microbial dysbiosis, increasing the relative abundance of oral bacteria Muribacter and Corynebacterium, as well as intestinal bacteria Lactobacillus, Romboutsia, and Limosilactobacillus, while decreasing the relative abundance of oral bacteria Rodentibacter, Rothia, and Streptococcus, and intestinal bacteria Ligilactobacillus and Desulfovibrio. Both oral and gut bacteria are closely associated with clinical inflammatory factors in GU. Following ulcer onset, decreased levels of NO, iNOS, PGE2, and MTL, alongside increased levels of TNF-α, IL-6, and MDA, directly induce a reduction in the abundance of bacteria, including Rothia, Streptococcus, Corynebacterium, Globicatella, Romboutsia, and Lactobacillus, with this effect being more pronounced in the oral cavity. However, treatment with RT may potentially increase the abundance of these bacteria within the intestine, which could directly regulate gastric ulcer-related inflammatory factor levels and ameliorate clinical symptoms. R. roxburghii root has therapeutic effects against the progression of gastric ulcers by promoting mucosal repair and suppressing the release of inflammatory mediators.